THE INFLUENCE OF COMPETENCE, COMPENSATION, AND WORK ENVIRONMENT ON PRODUCTIVITY MEDIATED BY EMPLOYEE WORK MOTIVATION AT PT MITRA TSALASA JAYA, SOUTH TANGERANG - Helen Syerah (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of competence, compensation, and work environment on employee productivity through work motivation as a mediating variable at PT Mitra Tsalasa Jaya, South Tangerang. Employee productivity is a key indicator of a company’s success, which is influenced by individual capabilities, performance rewards, and a supportive work environment. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 120 respondents, who are permanent employees of PT Mitra Tsalasa Jaya. The data were analyzed using path analysis to examine both direct and indirect relationships among the studied variables. The results showed that competence, compensation, and work environment have a positive and significant effect on work motivation. Furthermore, work motivation has a positive and significant effect on employee productivity. In addition, work motivation significantly mediates the influence of competence, compensation, and work environment on productivity. Therefore, the study concludes that improving employee competence, providing fair and appropriate compensation, and creating a conducive work environment can enhance employee motivation, which ultimately leads to higher productivity at PT Mitra Tsalasa Jaya.